The Comprehensive Systematic Review of Diagnosis and Management of Non Arteritic Anterior Ischemic Optic Neuropathy - Endah Tri Widanarti; Syarafina Kusmaheidi; Abdul Rahman; Bambang Setiohadji (The International Journal of Medical Science and Health Research, 2025)
Background: Non-Arteritic Anterior Ischemic Optic Neuropathy (NA-AION) is a leading cause of acute optic neuropathy and permanent vision loss in adults over the age of 50. This systematic review aims to provide a comprehensive analysis of the current understanding of NA-AION, including its pathophysiology, diagnostic approach, and management strategies. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: NA-AION remains a challenging condition with no definitive cure. Advances in imaging techniques, particularly OCT-A, have improved diagnostic accuracy and understanding of disease progression. Risk factor modification remains the cornerstone of management, with emerging therapies focusing on neuroprotection and vascular health. Further research is needed to develop targeted treatments and improve outcomes for patients with NA-AION.